2022
DOI: 10.2478/jvetres-2022-0048
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new emerging strain of rabbit haemorrhagic disease virus 2 (GI.2) in China

Abstract: Introduction In May 2020, an outbreak of rabbit haemorrhagic disease 2 (RHD2) caused by the rabbit haemorrhagic disease virus 2 (RHDV2, GI.2) occurred in Sichuan, China. The acute onset and short disease course resulted in rabbit mortality as high as 42.86%. Currently, basic research on the aetiology and genetic characteristics of GI.2 is lacking in China. Material and Methods Pathological changes in various tissues from infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…The NSP encoding genes of Lagoviruses determine the potential of virus replication and immune evasion (Urakova et al, 2015;Zhu et al, 2022), which is a complex process promoting virus evolution with frequent nucleotide variation (Silvério et al, 2018;Mahar et al, 2021). In this study, the recombination analysis reveals that the GI.1aP-GI.2 variants branches into a single clade, which possess similar molecular origins of the parental GI.1a and GI.2, indicating that this new recombination event may occur in China's RHDV strains after the outbreak of GI.2 in 2020 (Chen et al, 2022). Furthermore, the high nucleotide within these four variants also demonstrates that these novel recombinant strains have close geographical relationship.…”
Section: Genetic Recombination Inferred Evolutionary Adaption Of Gi1a...supporting
confidence: 49%
“…The NSP encoding genes of Lagoviruses determine the potential of virus replication and immune evasion (Urakova et al, 2015;Zhu et al, 2022), which is a complex process promoting virus evolution with frequent nucleotide variation (Silvério et al, 2018;Mahar et al, 2021). In this study, the recombination analysis reveals that the GI.1aP-GI.2 variants branches into a single clade, which possess similar molecular origins of the parental GI.1a and GI.2, indicating that this new recombination event may occur in China's RHDV strains after the outbreak of GI.2 in 2020 (Chen et al, 2022). Furthermore, the high nucleotide within these four variants also demonstrates that these novel recombinant strains have close geographical relationship.…”
Section: Genetic Recombination Inferred Evolutionary Adaption Of Gi1a...supporting
confidence: 49%
“…Rabbits were injected with GI.1, and Pasteurellosis multocida combined inactivated vaccine before and five days after the onset of rabbit farm, but the effect was not obvious 13 . In a previous study, we isolated a GI.2 strain SCCN04 from these dead rabbits at a rabbit farm in Jintang 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with pathogenic (variants GI.1a and GI.1b) and benign (genotype GI.4) strains that served as donors for the non-structural part while GI.2 composed the structural part. In our previous study 14 , we performed genetic characterization of SCCN04, where the whole genome phylogenetic tree, the non-structural phylogenetic genes tree and the structural genes phylogenetic tree were constructed, and recombination events were analysed. The results showed that SCCN04 and Chinese isolate SC2020/0401(MT586027.1) formed a small branch and were the most closely related among all the genome phylogenetic trees, and SCCN04 was closely related to European GI.2 isolates on a large branch.…”
Section: Introductionmentioning
confidence: 99%
“…In April 2020, the first RHDV2 outbreak occurred in rabbit farms located in the southwest of China [ 13 , 16 , 30 ]. Before that, the prevention and control of RHD had been effective and stable in local areas.…”
Section: Discussionmentioning
confidence: 99%